Segurança alimentar e nutricional de agricultoras familiares de Alenquer, Pará, Brasil: consumo alimentar e estado nutricional - SILVA, Luziene Santos da (Universidade Federal do Oeste do Pará, 2022)
This research is part of the debate on Food and Nutritional Sec urity FNS )), which in Brazil, instituted by L aw nº 11.346 / 2006, consists in realizing the right of everyone to regular and permanent access to quality food in sufficient quantity, without compromising access to other essential needs, based on health prom oting food practices that respect cultural diversity and are socially, economically and environmentally sustainable. Thus, its general objective was to analyze the situation of SAN in terms of food consumption and the nutritional status of family farmers f rom the Association of Small Rural Producers, Extractivists and Artisanal Fishermen of the municipality of Alenquer ASPROEXPA and as specific objectives: a) to identify production food in the family unit and access to the public FNS policy ; b) to invest igate the food consumption of the farmers and their families and c) to carry out a diagnosis of the nutritional status of the farmers and to identify the occurrence of diabetes and high blood p ressure in them. The field research followed the ethical precep ts according to CAEE nº 30185520.6.0000.5168, as well as the biosafety protocols established by the World Health Organization, to prevent community transmission of the new coronavirus. In this sense, one stage of the interviews was carried out by telephone and another in person, using as instruments of data collection for the investigation of food consumption: the 24 hour Food Recall Questionnaire, the Food Consumption Markers Form and the Scale Brazilian Food Insecurity EBIA )). Anthropometric measurements were collected to assess nutritional status: weight, height and waist circumference (abdominal). A questionnaire was also used to record self reported health information (diabetes and hypertension), socioeconomic and food production of the family unit. 14 women participated in the research, of which 71 4% (n = 10) presented inadequate nutritional status with diagnosis of overweight and obesity, according to the Body Mass Index (BMI) with substantially high risks of associated metabolic complications with ob esity (circumference). EBIA pointed out that 71 4% of the families of the participants in this study are in Food Security, that is, when there is no food restriction of any kind, not even the concern about the lack of food in the future. However, in the an alysis of current food consumption both by the 24 hour recall and by the Food Consumption Markers, it was found an inadequate diet with high consumption of ultra processed foods, which contributes to the appearance of diseases such as diabetes, high blood pressure and obesity, as well as, the inadequate nutritional status, reflected in the evaluation of the anthropometric measures of the participants of this research. Understanding the data on health and nutrition conditions, food consumption and access to public FNS programs enables Municipal Management, Universities and other institutions to promote FNS for research participants and the entire rural environment, in its concept broader guarantee of rights, with access, production, marketing and consumption of food and its relationship with health and quality of life.